2022
DOI: 10.1002/lio2.792
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic usefulness of cone‐beam computed tomography versus multi‐detector computed tomography for sinonasal structure evaluation

Abstract: Objective: Cone-beam computed tomography (CBCT) is a promising imaging modality for sinonasal evaluation, with advantages of relatively low radiation dose, low cost, and quick outpatient imaging. Our study aimed to compare the diagnostic performance and image quality of CBCT with those of multi-detector computed tomography (MDCT) with different slice thickness. Methods:We retrospectively reviewed 60 consecutive patients who had undergone both CBCT and MDCT. MDCT images was reconstructed with 1 and 3 mm slice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In line with the results of our study, M Han et al [ 22 ] in 2022, by examining CBCT findings on 60 patients, showed that, due to high accuracy, low radiation dose, and low cost, CBCT can be a useful method for initial evaluation and follow-up of patients who are candidates for cosmetic surgery. In their study, they also evaluated radiation dose and cost, while in our study, due to the study’s purpose, we could not estimate radiation dose and cost.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with the results of our study, M Han et al [ 22 ] in 2022, by examining CBCT findings on 60 patients, showed that, due to high accuracy, low radiation dose, and low cost, CBCT can be a useful method for initial evaluation and follow-up of patients who are candidates for cosmetic surgery. In their study, they also evaluated radiation dose and cost, while in our study, due to the study’s purpose, we could not estimate radiation dose and cost.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have shown that the use of cone beam computed tomography) CBCT (as one of the new methods has been of high accuracy in evaluating the structure of the nasal cavity, which can provide accurate and useful information about the bony structure of the nasal cavity and paranasal sinuses to the surgeon before rhinoplasty [ 17 , 21 ]. Many studies have shown that CBTC has a higher accuracy, lower radiation dose, and lower cost in diagnosing nasal abnormalities before rhinoplasty than other radiographic methods [ 19 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…With excellent detail of bony anatomy, cone beam CT (CBCT) additionally plays an important role in imaging of the paranasal sinuses for out clinic patients but is of very limited soft-tissue information. In CBCT, dose exposure is considered low [34][35][36][37]. However, this is only true when compared to CT examinations with dose exposures as low as 0.27 mSv [35]/ 0.6 mSv [34] and 4 mGy [37] and not when compared to sophisticated ultra-low-dose CT protocols [6].…”
Section: Plos Onementioning
confidence: 99%
“…In CBCT, dose exposure is considered low [34][35][36][37]. However, this is only true when compared to CT examinations with dose exposures as low as 0.27 mSv [35]/ 0.6 mSv [34] and 4 mGy [37] and not when compared to sophisticated ultra-low-dose CT protocols [6]. Conventional radiography no longer plays any real role in diagnosing the paranasal sinuses as the resulting images lack the detail and image quality required to visualize the relevant complex anatomy.…”
Section: Plos Onementioning
confidence: 99%
“…Cone beam CT (CBCT) is considered an alternative, especially for out-clinic patients, for assessing the paranasal sinuses for diagnosing chronic sinusitis and preoperative assessment [ 21 24 ]. Radiography has disadvantages because of the difficulty of delineating anatomy due to superimposition, and magnetic resonance imaging is not broadly available in the numbers needed, but is also an alternative, especially for soft tissue imaging.…”
Section: Introductionmentioning
confidence: 99%